An Investigation of the Educational Use of Facebook According to Physics Teachers and Students - Gök, Başak; Ünlü, Pervin (Journal of Education in Black Sea Region, 2021)
Today, social networks are used in every field of education, contributing to the dissemination of knowledge and improving the quality of education. This study investigated the perceptions of high school students, undergraduate students and physics teachers have on the adaptation of Facebook as a social network, the intended use of Facebook, and its educational use in a physics course. The participants included 327 high school students, 40 preservice physics teachers, and 28 physics teachers, all from Ankara, Turkey. The data revealed that there was a significant difference in the participants’ views on the adaptation of Facebook, the intended use of Facebook, and its educational use according to educational level, but not by gender. The teachers, compared to the high school students and the preservice teachers, scored significantly higher in the areas of adaptation of Facebook and its intended use. In the educational use of Facebook, the preservice teachers, compared to the high school students, and the teachers, compared to both high school students and preservice teachers, scored significantly higher. The variables of gender, educational level, intended use of Facebook, and its educational use were found to have a significant effect on the perceptions of the educational use of Facebook in physics education. In this study, while the use of Facebook in the field of education is not affected by gender in general, its use in physics education in specifically is affected by gender. Keywords: Facebook; Facebook in education; physics education